Big Book With Local Wisdom Yields Moderate Science Literacy Gains: Buku Besar Berisi Kebijaksanaan Lokal Menghasilkan Peningkatan Literasi Sains yang Moderat - Adenia, Arcelita Putri; Setiyawan, Enik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Science literacy is an essential competency for elementary students to understand scientific concepts and solve real-life problems in modern society. Specific Background However, national assessment reports indicate low science literacy performance among Indonesian students, while existing teaching materials rarely integrate contextual local culture with scientific content. Knowledge Gap Big Book media are commonly applied to early reading activities and are seldom developed as science literacy–oriented instructional materials linked to local wisdom. Aims This study aimed to develop and evaluate a Big Book on the Sidoarjo batik jetis local wisdom theme based on science literacy for fifth-grade students. Results Using the ADDIE development model with observation, interviews, questionnaires, and tests, the product achieved media expert validity of 87 percent and material expert validity of 73.9 percent, student practicality of 88.4 percent, teacher practicality of 80 percent, and an average N-Gain of 0.6 with a 60 percent moderate category. Novelty The Big Book integrates illustrated storytelling, heat transfer concepts, and local cultural practices within a structured science literacy framework. Implications These findings indicate that culturally contextual Big Book materials are feasible and suitable for supporting science learning in elementary classrooms. Keywords: Big Book, Local Wisdom, Science Literacy, ADDIE Model, Elementary Education Key Findings Highlights Expert appraisal confirmed high feasibility of the developed material Learner and teacher responses showed strong usability during classroom use Test scores displayed medium improvement after instructional application